2019
DOI: 10.1126/sciadv.aau7518
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and matrix viscoelasticity sequentially regulate endothelial progenitor cluster-based vasculogenesis

Abstract: Vascular morphogenesis is the formation of endothelial lumenized networks. Cluster-based vasculogenesis of endothelial progenitor cells (EPCs) has been observed in animal models, but the underlying mechanism is unknown. Here, using O2-controllabe hydrogels, we unveil the mechanism by which hypoxia, co-jointly with matrix viscoelasticity, induces EPC vasculogenesis. When EPCs are subjected to a 3D hypoxic gradient ranging from <2 to 5%, they rapidly produce reactive oxygen species that up-regulate proteases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 64 publications
21
82
0
Order By: Relevance
“…133 Within the liver, DPP4 is expressed in both hepatocytes and nonparenchymal cells, yet obesity only increases Dpp4 expression in hepatocytes. 134 Analysis by Baumeier et al 135 calculated by total weight predicted that in mice, the majority of DPP4 protein release came from the liver. Several groups have identified that circulating DPP4 levels are also positively associated with NAFLD.…”
Section: Dpp4 As a Biomarker Of Metabolic Liver Diseasementioning
confidence: 99%
“…133 Within the liver, DPP4 is expressed in both hepatocytes and nonparenchymal cells, yet obesity only increases Dpp4 expression in hepatocytes. 134 Analysis by Baumeier et al 135 calculated by total weight predicted that in mice, the majority of DPP4 protein release came from the liver. Several groups have identified that circulating DPP4 levels are also positively associated with NAFLD.…”
Section: Dpp4 As a Biomarker Of Metabolic Liver Diseasementioning
confidence: 99%
“…These fibroblast derived factors act to minimally stiffen gels (0.03-0.05 kPa) and are required for the lumenisation of sprouting vessels (Newman et al, 2011). In an elegant study by Blatchley et al (2019), thick 3D collagen gels were demonstrated to provide a temporal hypoxic gradient (Figure 2C), allowing for the study of EC behavior in response to changes in both hypoxia and ECM stiffness. These models have simultaneously revealed encapsulation of endothelial colony-forming cells (ECFCs) leads to vasculogenic cluster formation through ROS production in hypoxic (thick) but not normoxic (thin) collagen hydrogels (Figure 2C), and that increased matrix stiffness via collagen crosslinking leads to reduced cluster formation (Blatchley et al, 2019).…”
Section: Models To Study Ec Behavior Regulated Via Matrix Stiffness and Stretchingmentioning
confidence: 99%
“…(d) Reproduced with permission under the terms of the CC‐BY‐NC‐4.0 license. [ 141 ] Copyright 2019, the Authors. Published by the American Association for the Advancement of Science (AAAS).…”
Section: Applications Of Biomaterials To Study Fibrosismentioning
confidence: 99%
“…Microfluidic devices and tunable hypoxia‐inducing materials could be used to create oxygen gradients (Figure 7) in order to understand how oxygen availability couples with mechanical properties, such as stiffness and viscoelasticity, to promote fibrotic phenotypes. [ 139–141 ]…”
Section: Remaining Questions and Emerging Materials To Study Fibrosismentioning
confidence: 99%